MITO E MEMÓRIA NO FILME PUBLICITÁRIO "L´ODYSSÉE DE CARTIER" : ESTRUTURAS DE CRIAÇÃO - Lunkes, Rafaeli Francini (2014)
In conexion with cultural imaginary, mith is a fantastic text from narrative structure which concerns to the ancestrality of human languages. Being the first way of reality`s interpretation, the mith is a system built by ritual, totem and temporality which tends to present as a narrative. Basis of cultural texts, the mith remains, nowadays, in media structures from narrative features, among them, the advertising movie. From the movie L`Odyssée de Cartier, corpus of this resarch, it is intended to strengthen conceptions about fundamentals audiovisual languages and its relationship with culture, to think about mechanisms in which cultural memory works out in creating advertising contentes and, through theoretical assumptions from Culture`s Semiotics, to contribute for a critical view about the creation process of advertising from Language Studies. Thus, it was necessary to analyze the structure of sense which is existent in adverstising movie, but, mostly, verify approximations between mythical texts (memory area) and advertising (intertextuality area).